Geraniol suppresses prostate cancer growth through down‐regulation of E2F8. (28th September 2016) - Lee, Sanghoon; Park, Yu Rang; Kim, Su‐Hwa; Park, Eun‐Jung; Kang, Min Ji; So, Insuk; Chun, Jung Nyeo; Jeon, Ju‐Hong
Abstract: Geraniol, an acyclic dietary monoterpene, has been found to suppress cancer survival and growth. However, the molecular mechanism underlying the antitumor action of geraniol has not been investigated at the genome‐wide level. In this study, we analyzed the microarray data obtained from geraniol‐treated prostate cancer cells. Geraniol potently altered a gene expression profile and primarily down‐regulated cell cycle‐related gene signatures, compared to linalool, another structurally similar monoterpene that induces no apparent phenotypic changes. Master regulator analysis using the prostate cancer‐specific regulatory interactome identified that the transcription factor E2F8 as a specific target molecule regulates geraniol‐specific cell cycle signatures. Subsequent experiments confirmed that geraniol down‐regulated E2F8 expression and the knockdown of E2F8 was sufficient to suppress cell growth by inducing G2 /M arrest. Epidemiological analysis showed that E2F8 is up‐regulated in metastatic prostate cancer and associated with poor prognosis. These results indicate that E2F8 is a crucial transcription regulator controlling cell cycle and survival in prostate cancer cells. Therefore, our study provides insight into the role of E2F8 in prostate cancer biology and therapeutics. Abstract : Geraniol exerts chemotherapeutic activity against cancer. Microarray analysis from geraniol‐treated prostate cancer cells identified that E2F8 is a specific target molecule that regulates geraniol‐specific cell cycle signatures. E2F8 is required for growth of prostate cancer cells by regulating G2/M progression. Epidemiological analysis showed that E2F8 is up‐regulated in metastatic prostate cancer patients and is associated with poor prognosis. Our study provides potential role of E2F8 in prostate cancer biology and therapeutics.